AN ANALYSIS ON FINANCIAL FARMING EFFORT WORTHINESS OF KEPOK BANANA (Musa paradisiaca L. cv. Kepok) IN MALINAU SEBERANG VILLAGE, SUB – DISTRICT NORTH MALINAU, MALINAU DISTRICT. - Hendris Hendris (UPT Penerbitan Universitas Jember, 2012)
Banana is a famous horticulture plant among the Indonesian. Kepok Banana is one of tropical fruits that have a high potential for intensively managed agri - oriented. In Malinau Seberang village, farming kepok banana has been done since a long time ago, but the farmers is not able to count the costs and benefits obtained from the activity, and it is interesting to be researched, does kepok banana financially worthy to cultivate. Methods of the research is financial analysis to know the Net Present Value (NPV), Net Benefit Cost Ratio (Net B/C Ratio) and Internal Rate of Return (IRR). The data uses primary data and secondary data. The research shows a development of kepok banana farming in Malinau Seberang Village, North Malinau sub – district, Malinau District, East Kalimantan that can be categorized as a viable farms to be developed. This is indicated by Net Present Value (NPV) at 12% - 20%. It shows a positive value at Rp.12.370.733,96 - Rp. 2.196.519,05 where NPV>1, Net B/C ratio at 12% is 1,32 so Net B/C ratio>1, and IRR at 12% is 22,48% so IRR>12%. Each of these indicates a fulfillment of a developing farming financial of banana, especially kepok banana.